PENGARUH RANSUM YANG MENGANDUNG LIMBAH TAUGE FERMENTASI TERHADAP KECERNAAN SERAT KASAR, PROTEIN KASAR DAN ENERGI METABOLIS PADA ITIK LOKAL FASE STARTER - Galuh Arum Pangestu; R.I. Pujaningsih; I. Mangisah (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2018)
This research aimed to reviewing level of bean sprout fermented used in duck diet against crude fiber digestibility, crude protein digestibility and metabolic energy of diet. The research was proccessed using Complete Random Design (CRD) with four treatments and four replications. The parameters observed were crude fiber digestibility, crude protein digestibility and metabolic energy. The research material used was 48 male ducks with starter phase, treatment diet, flock cage, battery cage, feed tray, water tube, HCl, plasctic tray, scales, hygrometer, a set of proximate and gross energy analysis equipment. The research method consits two stages, the first stage was fermented of bean sprouts using 6% of Trichoderma harzianum for six days. The second phase was in vivo method with addition of bean sprout fermented in diet respectively T0 0%, T1 5%, T2 10% and T3 15%. The result data was tested by F test based on analysis of varians and if there was significant effect of treatment (P<0.05) followed by the test of least significance defferent (LSD). The result of effect of diet containing bean sprouts fermented were no affected (P>0.05) the crude fiber digestibility, crude protein digestibility and metabolic energy for starter phase of local ducks. Keywords : Bean Sprouts, Digestibility, Duck, Fermentation, Tricodherma harzianum.